2020
DOI: 10.1002/jcla.23341
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of circulating exosomes in human cancer: A meta‐analysis

Abstract: Background Cancer has become a public health problem with high morbidity and mortality. Recent publications have shown that exosomes can be used as potential diagnostic biomarkers of cancer. However, the diagnostic accuracy and reliability of circulating exosomes remain unclear. The present meta‐analysis was conducted to comprehensively summarize the overall diagnostic performance of circulating exosomes for cancer. Methods Eligible studies published up to June 27, 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Their work showed that transforming growth factor beta (TGFβ)1 expressed at the exosome surface induced differentiation from fibroblasts to tumor-promoting myofibroblasts which act pro-angiogenetic [ 20 , 21 ]. Furthermore, it was shown that the levels of circulating exosomes had a promising diagnostic potential in the context of pancreatic, hepatocellular, and ovarian carcinoma [ 22 , 23 ]. Also, the count of circulating exosomes has been demonstrated as a prognostic marker for lung cancer patients in a meta-analysis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their work showed that transforming growth factor beta (TGFβ)1 expressed at the exosome surface induced differentiation from fibroblasts to tumor-promoting myofibroblasts which act pro-angiogenetic [ 20 , 21 ]. Furthermore, it was shown that the levels of circulating exosomes had a promising diagnostic potential in the context of pancreatic, hepatocellular, and ovarian carcinoma [ 22 , 23 ]. Also, the count of circulating exosomes has been demonstrated as a prognostic marker for lung cancer patients in a meta-analysis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…One meta‐analysis that evaluated the overall diagnostic value of circulating exosomes in cancers demonstrated that tumor types and exosomes sources could lead to heterogeneity. 39 In detail, the sensitivity, specificity, and AUC in hepatocellular carcinoma and ovarian cancer are higher than those in other cancers. Compared with plasma‐derived exosomes, serum‐derived exosomes had a better diagnostic performance.…”
Section: Discussionmentioning
confidence: 97%
“…No significant difference between subgroups might be generated by too few studies included in this study. One meta‐analysis that evaluated the overall diagnostic value of circulating exosomes in cancers demonstrated that tumor types and exosomes sources could lead to heterogeneity 39 . In detail, the sensitivity, specificity, and AUC in hepatocellular carcinoma and ovarian cancer are higher than those in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that EVs with high sensitivity and specificity can be used as liquid biopsies in the diagnosis and prognosis of patients’ outcomes and responses to treatment [ 12 , 13 , 14 , 15 ]. Additionally, meta-analyses, a powerful statistical tool, have confirmed the clinical utility of EVs for cancer detection and prognoses [ 16 , 17 , 18 , 19 ]. Let us say, then, that EVs are cancer detection’s ‘ne plus ultra’.…”
Section: Prima Facie Of Extracellular Vesicles (Evs) In Cancermentioning
confidence: 99%